2000
DOI: 10.1007/s004410000241
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution electron-microscopic study of the relationship between human enamel and dentin crystals at the dentinoenamel junction

Abstract: The development of dentin and of enamel share a common starting locus: the dentinoenamel junction (DEJ). In this study the relationship between enamel and dentin crystals has been investigated in order to highlight the guiding or modulating role of the previously mineralized dentin layer during enamel formation. Observations were made with a high-resolution electron microscope and, after digitalization, image-analysis software was used to obtain digital diffractograms of individual crystals. In general no dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 26 publications
2
45
0
1
Order By: Relevance
“…Some authors claim that enamel crystals grow epitaxially on the preexisting dentine crystals because of a high continuity between enamel and dentine crystals (Arsenault and Robinson 1989;Hayashi 1992Hayashi , 1993. Others have shown that enamel crystals are formed at a given distance from the dentine surface (Simmer and Fincham 1995;Diekwisch et al 1995;Aoba 1996;Bodier-Houllé et al 2000) and could either reach dentine crystals by a subsequent growth (Takano et al 1996) or remain distant (Bodier-Houllé et al 2000;Dong and Warshawsky 1996). In addition, there are both a cementum-enamel junction (CEJ) (Wang et al 2006b), which is quite similar to DEJ, and a cementumdentine junction (CDJ) (Ho et al 2004(Ho et al , 2005Jang et al 2014).…”
Section: Teethmentioning
confidence: 99%
“…Some authors claim that enamel crystals grow epitaxially on the preexisting dentine crystals because of a high continuity between enamel and dentine crystals (Arsenault and Robinson 1989;Hayashi 1992Hayashi , 1993. Others have shown that enamel crystals are formed at a given distance from the dentine surface (Simmer and Fincham 1995;Diekwisch et al 1995;Aoba 1996;Bodier-Houllé et al 2000) and could either reach dentine crystals by a subsequent growth (Takano et al 1996) or remain distant (Bodier-Houllé et al 2000;Dong and Warshawsky 1996). In addition, there are both a cementum-enamel junction (CEJ) (Wang et al 2006b), which is quite similar to DEJ, and a cementumdentine junction (CDJ) (Ho et al 2004(Ho et al , 2005Jang et al 2014).…”
Section: Teethmentioning
confidence: 99%
“…A small deviation of crystal orientation across each prism can be observed in densely packed enamel apatite prisms. Small disorientation angles have also been identified between enamel and dentin crystals excluding epitactic relationships [113]. Several studies report that the ribbon-like shaped structures formed at the earliest stage of enamel formation include a non-crystalline mineral (ACP) and/or octacalcium phosphate (OCP) crystals, both potent precursors of enamel apatite [114,115].…”
Section: Formationmentioning
confidence: 99%
“…Beniash et al [116] hypothesize that this transformation can be triggered by proteolytic degradation of the enamel matrix proteins and suggest that the shape and organization of the mineral particles is determined very early, implying direct control of mineral shape and organization by the matrix proteins. Bodier-Houllé et al [113] have also identified the presence of amorphous calcium phosphate at the interface of enamel and dentin (dentino-enamel junction).…”
Section: Formationmentioning
confidence: 99%
See 2 more Smart Citations